Palestinian Readings as a Form of Educational Work of Imperial Orthodox Palestinian Society at Turn of 19th—20th Centuries - V. V. Tsys; O. P. Tsys (Научный диалог)
The article deals with the formation of the Palestinian Readings as the main form of cultural and educational work of the diocesan departments of the Imperial Orthodox Palestinian Society, the oldest public religious organization in Russia. It is noted that, although the first diocesan departments were created in 1893, their goal was only to increase the collection of donations for the needs of Russian pilgrims and institutions in the Holy Land. Only a few years later it was realized that the main and most important area of work should be religious and moral education, the dissemination of accurate and correct information about the Holy Land through specially held Palestinian readings. This evolution can also be traced in the materials submitted to the highest name and the chairman of the organization, Grand Duke Sergei Alexandrovich. The organizational stage as a whole did not last long: until the reporting year 1895—1896 (beginning on March 1), inclusive, although in some dioceses it could drag on for a longer period. As a result, from a means to compensate for the fall in revenues from the Faithful collection, the Palestinian readings become a means of Christian enlightenment of Orthodox Russian people.